Comparison of the Postoperative Pain, Septal Perforation and Synechiae Formation following Septoplasty done with Trans Septal Suturing Verus Nasal Packing - Aeimen Fatima, Sundas Masood, Asmara Hussain, Tahira Ikram, Fatima Shahid, Memoona Afzal (Journal of Rawalpindi Medical College, 2022)
Objective: To compare the efficacy of trans-septal suturing with nasal packing following septoplasty in patients with the deviated nasal septum, in terms of frequency of postoperative pain, septal perforation, and synechiae formation. Materials and Methods: A randomized controlled trial was conducted in the ENT department of Benazir Bhutto Hospital Rawalpindi. Patients were divided into two groups. The total sample size of the study was 280 patients with 1:1 randomization in each group (140 in each group). Consecutive non-probability sampling was used for the recruitment of patients. All the patients underwent a septoplasty. Group A was provided with nasal packing while group B was with trans septal suturing. The study duration was 1 year (21-11-2016 to 21-11-2017). All the patients were followed at 24 hours for measurement of postoperative pain and at 1 and 4 weeks for septal perforation and synechiae formation. Ethical approval was taken from the ethical review board and consent was taken from patients. Data were analyzed using SPSS version 22. The Chi-square test was applied for observing the association between different variables. Inclusion Criteria - Patients with deviated nasal septum. - Patients’ ages ranged from 17-35 years. - Patients of both genders were included. Exclusion Criteria - Patients with diabetes mellitus. - Patients with allergic rhinitis. - Patients with coagulopathies, pulmonary and cardiovascular disorders. - Patients taking warfarin, aspirin, or heparin. Results: Among all the patients 280 (100%), there were 123(43.9%) males and 157(56.1%) females. The study found that the mean age of patients was 25.3±11.9. In group A patients 140, 110 patients showed efficacy while 30 patients did not show efficacy during the study time period. Similarly, 124 patients showed efficacy in Group B while 16 patients did not show efficacy. A significant association was found in both groups regarding pain at 24 hours (p=0.00) while an insignificant association was found with age (p>0.05). Conclusion: To conclude, the trans-septal suturing technique applied in septoplasty causes minimal pain and complications like septal perforation and synechiae formation, and patients resume routine life activities shortly after the surgery. Keywords: Septoplasty, nasal packing, trans-septal sutures, nasal septal perforation.